Radon adsorption by zeolite. (January 2015) - Bikit, I.; Mrdja, D.; Bikit, K.; Grujic, S.; Knezevic, D.; Forkapic, S.; Kozmidis-Luburic, U.
Abstract: Due to well defined three dimensional nano- and micro-porous structure, one of the most important properties of zeolite is its surface adsorption capacity. Nevertheless, a natural zeolite adsorption capability of 222 Rn has not been thoroughly investigated. The objective of this paper is to review the research concerning the application of natural zeolite in 222 Rn adsorption. To achieve this goal the investigation based on measurements of radon adsorption by various zeolite granulation was done. Ball mill is used to achieve different granulations of zeolite in the range of μm–mm, whereas the particle size distributions are determined by particle size analyzer, Mastersizer 2000. The zeolite samples were exposed to elevated radon concentrations up to 1800 Bq/m 3 inside a closed chamber (volume ≈ 5.4 × 10 −3 m 3 ). The absorbed radon quantity was measured by high resolution gamma spectroscopy. The influence of particle size was measured and discussed. We found that the adsorption coefficients that were obtained in our experiment for natural zeolite samples for different granulations are similar to adsorbing coefficients for silica gel, but they are an order of magnitude lower than radon adsorbing coefficient for synthetic zeolite. The adsorption coefficient for activated charcoal derived in our experiment ( ≈ 3 m 3 /kg) is in average 50 times higher comparing to the adsorption coefficients obtained for zeolite samples (0.038 m 3 /kg–0.11 m 3 /kg). All adsorbing coefficients are determined for very low relative humidity of air of about 7%, since our simple experimental setup did not allow possibility to change the relative humidity, or temperature. In addition, we explored the perturbation of radon concentration inside small-volume radon chamber caused by the presence of adsorbing sample and influence of this perturbation on obtained values of adsorbing coefficients. Highlights: Measurements of radon adsorption by various zeolite granulation are done. Adsorption coefficients for natural zeolite and activated charcoal are determined. The adsorption coefficients for activated charcoal and natural zeolite are compared.